2022
DOI: 10.1186/s13567-022-01079-0
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of different TMEM154 genotypes in three Italian sheep breeds infected by different SRLV genotypes

Abstract: Small ruminant lentiviruses (SRLV) belong to the Retroviridae family and can cause various diseases. One of the most impacting diseases is visna-maedi, a complex disease characterized by long latencies and chronic progressive inflammatory events affecting the nervous system, lungs, mammary gland, and articular joints. A single nucleotide polymorphism (rs408593969, c.103G>A, missense mutation E35K) in the ovine transmembrane protein gene 154 (TMEM154) was identified as protective against small ruminant lenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
2
6
0
1
Order By: Relevance
“…The prospective cohort study results present here were entirely consistent with previous reports of retrospective matched cases control studies [ 4 , 13 ] and related prospective cohort studies [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 20 ]. Ewes with two copies of haplotype “1” show significantly reduced susceptibility to lentivirus infection compared to those with one or two copies of haplotypes “2” or “3” reported.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prospective cohort study results present here were entirely consistent with previous reports of retrospective matched cases control studies [ 4 , 13 ] and related prospective cohort studies [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 20 ]. Ewes with two copies of haplotype “1” show significantly reduced susceptibility to lentivirus infection compared to those with one or two copies of haplotypes “2” or “3” reported.…”
Section: Discussionsupporting
confidence: 92%
“…The deletion haplotype “4” typically has a frequency less than 5% in sheep populations and has not been rigorously tested for association with infection. However, these association with haplotypes “1”, “2”, and “3” have been reproduced around the world with different sheep populations, viruses, and management environments [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. While other sheep variants have been reported to be associated with OPP, replication and validation in prospective challenge studies is lacking [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that the host’s genetic background plays an important role in determining susceptibility or resistance to SRLV infection and pathogenesis. Some breeds (Texel, Border Leicester, Finnish Landrace, Biellese, Churra and Assaf) are more susceptible to SRLV infection than others (Rabouillet, Île de France, Suffolk Columbia, Rambo, Polipay, Delle Langhe, Bergamasca, Raza Navarra and Aragonesa) ( 69 , 83 , 106 , 147 ). Furthermore, many authors reported the presence of loci linked to SRLV susceptibility or resistance, such as ZNF389 ( 174 ), DRB1 ( 85 ), TLR9 ( 160 ), DPPA2/DPPA4 and SYTL3 ( 173 ), TMEM154 ( 69 ) and CCR5 ( 175 ).…”
Section: Tropism and Pathologymentioning
confidence: 99%
“…( 103 ) and Moretti et al . ( 106 ) suggested that the relationship between the single nucleotide polymorphism (SNP) TMEM154_E35K and susceptibility or resistance must be treated with caution, since in the German Merinoland breed and the Italian Biellese, Delle Langhe and Bergamasca breeds, a large number of sheep with the less susceptible genotype were seropositive. Ramirez et al .…”
Section: Tropism and Pathologymentioning
confidence: 99%
“…Isso pode estar relacionado com a existência de outras mutações no gene TMEM154 diferentes da E35K tais como D33N, T44M, I70N ou G38R, porém os envolvimentos desses SNPs individualmente ou juntamente são ainda considerados desconhecidos para susceptibilidade a LVPR(RAMÍREZ et al, 2021). Foi observado que nenhum vírus do genótipo A foi encontrado em ovinos com o genótipo KK, independentemente da raça, que é consistente com o fator de proteção, enquanto que poderia haver uma potencial susceptibilidade em animais carregando pelo menos um alelo (EE ou EK) em infecções causadas pelo genótipo B e E(MORETTI et al, 2022). podem também contribuir para a replicação viral.…”
unclassified